2011
DOI: 10.1177/0192513x11425459
|View full text |Cite
|
Sign up to set email alerts
|

The Separate Spheres of Online Health

Abstract: The objective of this article is to explore how parental status, gender, and their interaction influence a variety of aspects of searching for online health information. Drawing on nationally representative survey data, the results show that in a number of ways parenting and gender have separate but significant influences on the following: online searching behavior, whether the information is used, and feelings about the information obtained. The authors found that although female parents are more likely than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 34 publications
1
14
1
Order By: Relevance
“…One study found that men and people without children were more likely to seek health information for themselves rather than others [56]. The relatively small proportion of males (27.84%, 1133/4070) coupled with the low online HISB may have influenced the ability to detect gender differences even in our large sample.…”
Section: Discussionmentioning
confidence: 83%
“…One study found that men and people without children were more likely to seek health information for themselves rather than others [56]. The relatively small proportion of males (27.84%, 1133/4070) coupled with the low online HISB may have influenced the ability to detect gender differences even in our large sample.…”
Section: Discussionmentioning
confidence: 83%
“…A considerable number of the studies reviewed cover the issue of gender, but mostly as part of a larger set of demographic attributes (see Table 5); some authors agree that women use and trust the Internet more than men when it comes to health problems [45,67,79-82]. However, a number of studies showed no differences [66,83-85], leaving the gender debate open and in need of further research.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies showed no differences [66,83-85], leaving the gender debate open and in need of further research. Only two studies focus on gender differences in online health searches behavior: one from Korea [67]and one from the United States [82]. In contrast, the role of gender in influencing online trust judgments, in contexts other than health, has received more attention (eg, [100,101]).…”
Section: Discussionmentioning
confidence: 99%
“…The NTIA (2011) also reports parity between sexes in both Internet access and broadband access, and PEW reports that no differences exist in the number of men and women who use social networking sites (Zickuhr & Smith, 2012). Regarding online information seeking, women have been found to search more for health information than men (Stern, Cotten, & Drentea, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%